Antitumor efficacy of interferon‐γ‐modified exosomal vaccine in prostate cancer. Issue 11 (19th May 2020) - Shi, Xiaojun; Sun, Jie; Li, Haoran; Lin, Hao; Xie, Weiwei; Li, Jinlong; Tan, Wanlong
Abstract: Background: Exosomes secreted by tumor cells can be regarded as carriers of tumor‐associated antigens and have potential value in tumor immunotherapy. The aim of this study was to evaluate the antitumor efficacy of a novel exosomal vaccine (interferon‐γ [IFN‐γ]‐modified exosomal vaccine) in prostate cancer. Methods: Prostate cancer cell‐derived exosomes were used to prepare the exosomal vaccine using our protein‐anchoring technique. The immunogenicity and therapeutic efficacy of the exosomes was evaluated by measuring the effects of the exosomal vaccine on M1 macrophage differentiation, the ability of macrophages to engulf the exosomes, the production of antibodies against exosomes, and tumor angiogenesis and metastasis, and tumor growth. Results: The IFN‐γ fusion protein was efficiently anchored on the surface of prostate cancer cell‐derived exosomes and retained its bioactivity. The IFN‐γ‐exosomal vaccine increased the number of M1 macrophages, enhanced the ability of M1 macrophages to engulf RM‐1 cell‐derived exosomes, and induced the production of specific antibodies against exosomes. The exosomal vaccine downregulated the expression of vascular endothelial growth factor receptor 2 and attenuated the effect of exosomes in promoting tumor metastasis. The proportions of CD4 +, CD8 +, and IFN‐γ + CD8 + T cells in the exosomal vaccine group were the highest among the four groups. Interestingly, the IFN‐γ‐exosomal vaccine decreased the percentage of Tregs and downregulated the expression of programed death‐ligand 1 and indoleamine 2, 3‐dioxygenase 1 in the tumor environment. The exosomal vaccine significantly inhibited tumor growth and prolonged the survival time of mice with prostate cancer. The exosomal and tumor cell vaccines had a good synergistic effect in promoting tumor immunity. Conclusions: The novel exosomal vaccine induced an immune response that cleared prostate cancer cell‐derived exosomes, thereby eliminating the regulatory effect of the exosomes. This study may provide experimental evidence for the use of exosomes as a therapeutic tool or target in immunotherapy for human prostate cancer.